Evolutionary Significance of Wolbachia-to-Animal Horizontal Gene Transfer: Female Sex Determination and the f Element in the Isopod Armadillidium vulgare - Cordaux, Richard (Genes (Basel), 2017)
An increasing number of horizontal gene transfer (HGT) events from bacteria to animals have been reported in the past years, many of which involve Wolbachia bacterial endosymbionts and their invertebrate hosts. Most transferred Wolbachia genes are neutrally-evolving fossils embedded in host genomes. A remarkable case of Wolbachia HGT for which a clear evolutionary significance has been demonstrated is the “f element”, a nuclear Wolbachia insert involved in female sex determination in the terrestrial isopod Armadillidium vulgare. The f element represents an instance of bacteria-to-animal HGT that has occurred so recently that it was possible to infer the donor (feminizing Wolbachia closely related to the wVulC Wolbachia strain of A. vulgare) and the mechanism of integration (a nearly complete genome inserted by micro-homology-mediated recombination). In this review, we summarize our current knowledge of the f element and discuss arising perspectives regarding female sex determination, unstable inheritance, population dynamics and the molecular evolution of the f element. Overall, the f element unifies three major areas in evolutionary biology: symbiosis, HGT and sex determination. Its characterization highlights the tremendous impact sex ratio distorters can have on the evolution of sex determination mechanisms and sex chromosomes in animals and plants.